2012
DOI: 10.1515/znc-2012-9-1004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of Novel Benzoxazoles

Abstract: A series of 2-(p-substituted-benzyl)-5-[[4-(p-chloro/fluoro-phenyl)piperazin-1-yl]ace tamido] -benzoxazoles were synthesized in need of new compounds for the fight against microbial pathogens. Their structures were elucidated by spectral techniques. These new derivatives, along with previously synthesized 2-(p-substituted-benzyl)-5-substituted-benzoxazoles, were evaluated for their antibacterial and antifungal activities against standard strains and drugresistant isolates in comparison with ampicillin, gentami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…In addition, benzoxazole derivatives possess a variety of biological activities such as antitumor [ 112 , 113 , 114 , 115 ], antituberculosis [ 116 ], antifungal [ 117 ], antimicrobial [ 118 , 119 , 120 , 121 , 122 , 123 ], antihypertension [ 124 ], antiviral [ 97 , 125 ], antihormonal [ 126 ], and radioligand agents [ 127 , 128 , 129 ]. Because of the aforementioned properties of both fluorine and benzazoles, efforts have been done by Nosova et al to summarize several methods of synthesizing fluorinated benzazoles [ 130 ].…”
Section: Benzazolesmentioning
confidence: 99%
“…In addition, benzoxazole derivatives possess a variety of biological activities such as antitumor [ 112 , 113 , 114 , 115 ], antituberculosis [ 116 ], antifungal [ 117 ], antimicrobial [ 118 , 119 , 120 , 121 , 122 , 123 ], antihypertension [ 124 ], antiviral [ 97 , 125 ], antihormonal [ 126 ], and radioligand agents [ 127 , 128 , 129 ]. Because of the aforementioned properties of both fluorine and benzazoles, efforts have been done by Nosova et al to summarize several methods of synthesizing fluorinated benzazoles [ 130 ].…”
Section: Benzazolesmentioning
confidence: 99%
“…Recently, Temiz‐Arpaci group published two articles describing a series of 2‐phenyl/benzyl substituted benzoxazoles with potent antimicrobial activity ,. Firstly, they described the synthesis of series of benzyl substituted benzoxazoles 5 and their antitubercular activity against MTB and its isolate (Table ) . Further, authors suggested that a [4‐( p‐ chloro/fluoro‐phenyl)piperazin‐1‐yl]acetamido moiety in position 5 might permit an easier penetration through the lipophilic mycobacterial cell wall.…”
Section: Benzoxazoles As Anti‐tb Agentsmentioning
confidence: 99%
“…In recent years, we have described the synthesis of various derivatives of some 2,5-disubstituted benzoxazoles and their in vitro antimicrobial activity against some Gram-positive and Gram-negative bacteria and the fungus Candida albicans (Temiz-Arpaci et al, 2002a, b, 2008Alper-Hayta et al, 2008;Arisoy et al, 2012). In the present study, we aimed to develop new effective antitubercular and antimicrobial agents possessing benzoxazole nuclei in their structure.…”
Section: Introductionmentioning
confidence: 99%